A Study on Mughal Military Revolution: Unveiling the Transformation of Warfare in the Mughal Empire (Journal of Advances and Scholarly Researches in Allied Education, 2014)
This doctoral study, Mughals at War: Babur, Akbar and the Indian Military Revolution, examines the transformation of warfare in South Asia during the foundation and consolidation of the Mughal Empire. It emphasizes the practical specifics of how the Imperial army waged war and prepared for war—technology, tactics, operations, training and logistics. These are topics poorly covered in the existing Mughal historiography, which primarily addresses military affairs through their background and context cultural, political and economic. I argue that events in India during this period in many ways paralleled the early stages of the ongoing "Military Revolution" in early modern Europe. The Mughals effectively combined the martial implements and practices of Europe, Central Asia and India into a model that was well suited for the unique demands and challenges of their setting.